Different Levels of Incomplete Terminal Pathway Inhibition by Eculizumab and the Clinical Response of PNH Patients - Harder, Markus J.; Höchsmann, Britta; Dopler, Arthur; Anliker, Markus; Weinstock, Christof; Skerra, Arne; Simmet, Thomas; Schrezenmeier, Hubert; Schmidt, Christoph Q. (Frontiers in Immunology, 2019)
Background: Eculizumab blocks the lytic complement pathway by inhibiting C5 and has become the standard of care for certain complement-mediated diseases. Previously, we have shown that strong complement activation in vitro overrides the C5 inhibition by Eculizumab which accounts for residual terminal pathway activity. Results: Here we show that the levels of residual hemolysis in ex vivo assays differ markedly (up to 3.4-fold) across sera collected from different paroxysmal nocturnal hemoglobinuria (PNH) patients on Eculizumab treatment. This large variability of residual activities was also found in sera of healthy donors, thus cross-validating the findings in patients. While PNH patients with residual lytic activities of 11-30% exhibited hemolysis levels around the upper limit of normal (i.e. plasma LDH of ~250 u/L), as expected for PNH patients on Eculizumab therapy, we found sustained and markedly increased LDH levels of around 400 u/L for the patient with the highest residual activity of 37%. Furthermore, the clinical history of nine out of 14 PNH patients showed intravascular breakthrough hemolysis at the time of documented infections despite ample amounts of administered Eculizumab and/or experimentally determined excess over C5. Conclusion: The occurrence of extraordinary high levels of residual terminal pathway activity in PNH patients receiving Eculizumab is rare, but can impair the suppression of hemolysis. The commonly observed low levels of residual terminal pathway activity seen for most PNH patients can exacerbate during severe infections and, thus, can cause pharmacodynamic breakthrough hemolysis in PNH patients treated with Eculizumab.